Tumbo lisiloshiba na hadithi nyingine - Chokocho, Alifa, Alifa Chokocho; Chokocho, Alifa; Kayanda, Dumu (Nairobi, Kenya : Sasa Sema chapa ya Longhorn Publishers, 2016)
Short stories.
In Swahili
In Swahili.